2020
DOI: 10.1016/j.ctro.2020.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy for elder patients aged ≥80 with clinically localized prostate cancer – Brachytherapy enhanced late GU toxicity especially in elderly

Abstract: Background and purpose: Elongation of life expectancy had led to marked increase in number of elderly patients with localized prostate cancer. However, the standard treatment for such patients is not well determined because of a high prevalence of comorbidities and slow growth of prostate cancer. The aim of this study is to examine the feasibility of radiotherapy for elderly patients aged !80 years. Materials and methods: We compared 96 patients aged !80 years and 2333 younger patients (aged 60-79 years) using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
(31 reference statements)
2
9
0
Order By: Relevance
“…In the first study (>75y), bNED was significantly higher after BT compared to IMRT, particularly for high-risk patients (91.2% vs 73.6%; p = 0.0195) [30] . In the second study (>80y), the authors reported similar 5-y OS in > 80y (MA 81y) and younger patients (MA 71y): 97.8% vs 96.4% (p = 0.4202) [31] .…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…In the first study (>75y), bNED was significantly higher after BT compared to IMRT, particularly for high-risk patients (91.2% vs 73.6%; p = 0.0195) [30] . In the second study (>80y), the authors reported similar 5-y OS in > 80y (MA 81y) and younger patients (MA 71y): 97.8% vs 96.4% (p = 0.4202) [31] .…”
Section: Resultsmentioning
confidence: 80%
“…With a MFU of 3.3 years, no difference was noted in acute toxicity or in late GI toxicity. (G2: 8% vs 3% p = 0.19) [31] . Nevertheless, the authors reported an increased late G2 GU toxicity (22% vs 8%; p = 0.005) [38] .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…With a MFU of 71.6 months, the authors reported an estimated bRFS and OS at 72 months of 85.7% and 88.3%. Yamazaki et al [30,31] in their two studies comparing younger and elderly pts (>75 y then 80 y) with all risk PC, reported comparable outcomes in the cohorts with no impact of age. However, in a retrospective study including 2701 pts > 80 y treated with BT (77% with IR or HR-PC), Valdivieso R et al [32] analyzed the oncological outcome at 5 and 10 years.…”
Section: Discussionmentioning
confidence: 97%